Excursions in the 14C record at A.D. 774–775 in tree rings from Russia and America. Issue 8 (25th April 2014) - Jull, A. J. Timothy; Panyushkina, Irina P.; Lange, Todd E.; Kukarskih, Vladimir V.; Myglan, Vladimir S.; Clark, Kelley J.; Salzer, Matthew W.; Burr, George S.; Leavitt, Steven W.
Abstract The calibration of radiocarbon dates by means of a master calibration curve has been invaluable to Earth, environmental and archeological sciences, but the fundamental reason for calibration is that atmospheric radiocarbon content varies because of changes in upper atmosphere production and global carbon cycling. Improved instrumentation has contributed to high‐resolution (interannual) radiocarbon activity measurements, which have revealed sudden and anomalous activity shifts previously not observed at the common resolution of 5–10 years of most of the calibration scale. One such spike has been recently reported from tree rings from Japan and then again in Europe at A.D. 774–775, for which we report here our efforts to both replicate its existence and determine its spatial extent using tree rings from larch at high latitude (northern Siberia) and bristlecone pine from lower latitude (the White Mountains of California). Our results confirm an abrupt ~ 15‰ 14C activity increase from A.D. 774 to 776, the size and now the hemispheric extent of which suggest that an extraterrestrial influence on radiocarbon production is most likely responsible.